Regulating Strategies for Producing Carbohydrate Active Enzymes by Filamentous Fungal Cell Factories - Zhang, Teng; Liu, Hu; Lv, Bo; Li, Chun (Frontiers in Bioengineering and Biotechnology, 2020)
Filamentous fungi are important eukaryotic organisms crucial in substrate degradation and carbon cycle on the earth, and have been harnessed as cell factories for the production of proteins and other high value-added products in recent decades. As cell factories, filamentous fungi play a crucial role in industrial protein production as both native hosts and heterologous hosts. In this review, the regulation strategies of carbohydrate active enzymes expression at both transcription level and protein level are introduced, and the transcription regulation are highlighted with induction mechanism, signaling pathway, promoter and transcription factor regulation. Afterwards, the regulation strategies in protein level including suitable post-translational modification, protein secretion enhancement and protease reduction are also presented. Finally, the challenges and perspectives in this field are discussed. In this way, a comprehensive knowledge regarding carbohydrate active enzymes production regulation at both transcriptional and protein levels are provided with the particular goal of aiding in the practical application of filamentous fungi for industrial protein production.